Paediatric penile perception score (PPPS) in hypospadias repair - Syed Adeel Ahmed; Syed Zafar Zaidi (Journal of the Pakistan Medical Association, 2022)
The present cross-sectional study sought to evaluate the Paediatric Penile Perception Score (PPPS) as a tool to assess parental perception of hypospadias repair in children. In all, 60 patients were enrolled in the study with median age of 3.9 years; of these 24 (40%) had proximal hypospadias and 36 (60%) had distal hypospadias. After hypospadias repair, parents/guardians were interviewed about meatus, glans, skin, and general appearance using a standardised questionnaire to report penile appearance and penile perception. Overall, the median PPPS score was 17 (IQR: 16-18) with no significant difference in the penile perception score between the type of hypospadias, relationship of the person interviewed with the child (mother, father or other), nor the children’s age. The study revealed that penile perception score (PPPS) is a valuable tool that can be used to assess parental penile perception regarding the child’s penile appearance and noted overall high satisfaction after hypospadias repair. Keywords: Hypospadias, paediatric penile perception score (PPPS).